P126 Prevalence and correlates of fearing a partner during the COVID-19 pandemic in Britain: Findings from Natsal-COVID. (16th June 2022) - Tanton, Clare; Willis, Malachi; Conolly, Anne; Baxter, Andrew; Pérez, Raquel Bosó; Riddell, Julie; Dema, Emily; Copas, Andrew; Macdowall, Wendy; Bonell, Chris; Mercer, Cath; Sonnenberg, Pam; et al.
Abstract : Introduction: The COVID-19 pandemic and lockdown restrictions (e.g., only interacting within households) induced personal and relationship stressors, which might create conditions that increase intimate partner violence (IPV). We estimated the prevalence and correlates of experiencing IPV in the first year of the pandemic. Method: We used data from the Natsal-COVID Wave 2—a web-panel survey undertaken one year after the initial British lockdown from 23 March 2020. Quotas and weighting were used to achieve a quasi-representative sample of the British general population. Participants were asked about fearing a partner, which is a simple and effective way to identify IPV experiences. Results: In our sample (n = 6302), 9.0% of women and 8.7% of men reported fearing a partner in the first year of the pandemic—about three-quarters of whom reported this occurring more than once. Sociodemographic characteristics associated with fearing a partner during this period included being younger, having had a same-sex sexual partner in the past five years, and being in a relationship. Fearing a partner reportedly affected most of these participants in multiple aspects of their lives. Controlling for age, women (73.3%) were more likely than men (49.9%) to indicate that fearing a partner made them feel anxious or depressed; men were more likely to report increased substance use (30.8% vs. 18.4%) and affected work/studies (30.0% vs. 20.0%). Discussion: Population-level estimates of IPV during the pandemic highlight harmful experiences that occurred alongside other wide-ranging hardships, and the associations presented identify key populations with potential ongoing need.